Advances in PGPR Research 2017
DOI: 10.1079/9781786390325.0364
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the dual applications of Trichoderma spp. as biopesticide and biofertilizer.

Abstract: This chapter discusses Trichoderma biodiversity and potent isolate identification for applying as a biological control agent. The main modes of action of Trichoderma spp. are described, i.e. mycoparasitism of fungal pathogens with subsequent release of cell-wall-degrading enzymes such as cellulases, glucanases, chitinases, etc., and antibiosis by secretion of antimicrobial secondary metabolites and competition for nutrients. The application of Trichoderma spp. as biofertilizers is also discussed. Commercial fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…The results of this study as well as reported by Ramli et al [22] both biopertilizers were not only as plant growth promoter but also as biopesticide. Singh et al [23] reported that Trichoderma spp. also has a dual function.…”
Section: Population Density Of Generation One (G1)mentioning
confidence: 99%
“…The results of this study as well as reported by Ramli et al [22] both biopertilizers were not only as plant growth promoter but also as biopesticide. Singh et al [23] reported that Trichoderma spp. also has a dual function.…”
Section: Population Density Of Generation One (G1)mentioning
confidence: 99%